Manajemen Perubahan Berbasis Teknologi dalam Meningkatkan Efektivitas Sistem Pembelajaran Kitab Kuning di Pondok Pesantren Darun Nun Malang - Fuad Ali Maskur; Fasha Fatkurramah; Ayunda Pramuditya Fithrotunnada; Andri Ansyah; Shobihatul Fitroh Noviyanti (Al-Kindi, 2026)
Change management based on technology integration in Islamic education is an important strategy in responding to contemporary development dynamics, particularly in the kitab kuning learning system in Islamic boarding schools (pesantren). Empirical evidence shows that the dominance of traditional teaching methods remains an obstacle in optimizing the effectiveness of the learning system and students’ understanding of the material. Therefore, a planned change process is needed through a change management approach to integrate technology effectively into the learning system. This study aims to examine how technology-based change management can improve the effectiveness of the kitab kuning learning system at Darun Nun Islamic Boarding School, Malang. The novelty of this research lies in applying change management principles that combine traditional learning methods with digital technology as a strategy to enhance the quality of the pesantren learning system. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The findings indicate that the use of technology such as projectors can increase student participation, clarify material delivery, and create a more interactive learning system. In addition, gradual implementation of change can minimize resistance to innovation. However, challenges remain, including limited infrastructure and human resource readiness to support technology integration. This study contributes to developing an adaptive, integrative, and sustainable pesantren learning system model.